Effect of Azospirillum sp. and nutrients on yield of black pepper (Piper nigrum L.) - K S Krishnamurthy, K Kandiannan, C K Thankamani, V Srinivasan, (Journal of Spices and Aromatic Crops, 2011)
An experiment was conducted at Peruvannamuzhi (Kerala) to study the effect of Azospirillum sp. along with nutrients such as nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), zinc (Zn), boron (B) and molybdenum (Mo) on yield of black pepper (Piper nigrum). Maximum fresh yield (2207 g vine-1) was recorded in the treatment Azospirillum sp. + 50% recommended N + Mg followed by application of NPK alone. Significantly higher N, K and Mg content in the soil and N and Ca content in the leaf was observed in the treatment, 50% recommended N + Mg. Application of Azospirillum sp. increased the population of bacteria and a final population of 106 x 105 cfu (colony forming units) in the soil was recovered in the treatment 50% recommended N + Mg (0.2 kg ha-1) compared to uninoculated control.